Comparison of Spatial Planning of Sundanese Traditional Houses - Muzaki, Mutiara Silmi; Isfiaty, Tiara (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
This study aims to describe the differences and similarities in the spatial patterns of Sundanese traditional houses in Cikondang and Kampung Naga which are presented in the form of a comparison table. In making Sundanese traditional house in Cikondang and Kampung Naga, based on Sundanese customs rules, one of which is applied to the spatial pattern. The method used in this study is descriptive analysis by obtaining data through surveys and observations. This research combines the spatial layout in Sundanese traditional house in Cikondang with that in Kampung Naga. Includes spatial patterns and the number of spaces, space functions, users, dimensions, and number of openings. The results of the study found differences in terms of spatial patterns, space dimensions, users and the number of openings. Through this research, it can be concluded that there are differences in the spatial pattern of the cikondang traditional house has 2 pawon, namely the outer and inner pawon and has bale-bale located outside the core house building whose user is a woman. In terms of the number of openings, the Cikondang traditional house has 1 door while the Kampung Naga traditional house has 2 doors, namely the kitchen door and the main door